ANALISIS KERAPATAN VEGETASI MENGGUNAKAN METODE NDVI DI KECAMATAN BANGUNTAPAN KABUPATEN BANTUL - Muhammad Irvan Aditiya (Jurusan Pendidikan Geografi Universitas Negeri Manado, 2021)
The density of vegetation in an area is an influence on the lives of both humans and the environment. With vegetation density can also find out how changes in land use in an area. This study aims to determine the level of vegetation density in Banguntapan District in 2000 and 2020 using NDVI. The method used is interpretation of Landsat imagery with NDVI and the results will be classified according to the classification of vegetation density. The result is that the vegetation density in 2000 experienced a considerable decline in 2020 so that the vegetation in Banguntapan District was categorized as sparse to no vegetated, there was a change in land use for 20 years and the area turned into a built area, this was followed by the development of the number and activities of the population.